Tax management in the conditions of the crisis (Journal of Economic Research & Business Administration, 2022)
The article is devoted to the study of the problems of state tax management in the Republic of Kazakhstan.The initial condition is the absence of uniform methodological and methodical approachesto the formation and organization of tax management, including in conditions of extreme economicinstability. The main research methods used were: analysis and synthesis, systemic and institutional approaches,methods of induction and deduction, the method of designing hypotheses. The directions ofmodernization of the tax regulation system, the impact of mechanisms, methods and tools of tax managementon various segments of the national economy, primarily on the industries that ensure economicgrowth, have been investigated. In order to improve the efficiency of fiscal regulation, a scenario modelingis proposed, which makes it possible to assess the effect of the implementation of various situationson fiscal revenues and key macroeconomic indicators. The result of the study is the development ofdirections, measures of economic, administrative, financial, political development of the modern levelof tax management based on the analysis of the current state of the national tax system, scenario modeling,as well as the empirical design of the strategic SWOT analysis matrix. The theoretical and practicalsignificance of the study lies in substantiating the need for adaptive tax regulation and tax managementin order to ensure sustainable growth of the national economy.Key words: tax regulation, crisis, tax system, sustainable economic growth, scenario modeling.